A Deep Transfer Learning Strategy for Identifying Photovoltaic Panels Mounted on Building Rooftops from Orthophotos - A. M. Freitas Junior, Marco; A. S. Fernandes, Ricardo (Revista de Informática Teórica e Aplicada, 2026)
This work presents an analysis of orthophotos, which were used to train a predictive model based on a Convolutional Neural Network with the objective of identifying the presence of photovoltaic panels on building rooftops. To this end, the dataset named as Kortviseren, from Denmark, was used, which contains images of rooftops with and without photovoltaic panels. From this dataset, a convolutional neural network ResNet18 was employed, whose synaptic weights were adjusted through transfer learning. During the validation process, it was possible to observe a f1-score of approximately 98,7%. The results demonstrated the feasibility of the proposed approach for identifying photovoltaic panels mounted on building rooftops and, consequently, supporting power distribution utilities with the inspection of these consumer units that have the capacity to produce electricity.